Substantial Cardiovascular Morbidity in Adults With Lower-Complexity Congenital Heart Disease. Issue 16 (16th April 2019) - Saha, Priyanka; Potiny, Praneetha; Rigdon, Joseph; Morello, Melissa; Tcheandjieu, Catherine; Romfh, Anitra; Fernandes, Susan M.; McElhinney, Doff B.; Bernstein, Daniel; Lui, George K.; Shaw, Gary M.; Ingelsson, Erik; et al.
Abstract : Background: Although lower-complexity cardiac malformations constitute the majority of adult congenital heart disease (ACHD), the long-term risks of adverse cardiovascular events and relationship with conventional risk factors in this population are poorly understood. We aimed to quantify the risk of adverse cardiovascular events associated with lower-complexity ACHD that is unmeasured by conventional risk factors. Methods: A multitiered classification algorithm was used to select individuals with lower-complexity ACHD and individuals without ACHD for comparison among >500 000 British adults in the UK Biobank. ACHD diagnoses were subclassified as isolated aortic valve and noncomplex defects. Time-to-event analyses were conducted for the primary end points of fatal or nonfatal acute coronary syndrome, ischemic stroke, heart failure, and atrial fibrillation and a secondary combined end point for major adverse cardiovascular events. Maximum follow-up time for the study period was 22 years with retrospectively and prospectively collected data from the UK Biobank. Results: We identified 2006 individuals with lower-complexity ACHD and 497 983 unexposed individuals in the UK Biobank (median age at enrollment, 58 [interquartile range, 51–63] years). Of the ACHD-exposed group, 59% were male, 51% were current or former smokers, 30% were obese, and 69%, 41%, and 7% were diagnosed or treated for hypertension, hyperlipidemia, and diabetes mellitus, respectively. After adjustment for 12 measured cardiovascular risk factors, ACHD remained strongly associated with the primary end points, with hazard ratios ranging from 2.0 (95% CI, 1.5–2.8; P <0.001) for acute coronary syndrome to 13.0 (95% CI, 9.4–18.1; P <0.001) for heart failure. ACHD-exposed individuals with ⩽2 cardiovascular risk factors had a 29% age-adjusted incidence rate of major adverse cardiovascular events, in contrast to 13% in individuals without ACHD with ≥5 risk factors. Conclusions: Individuals with lower-complexity ACHD had a higher burden of adverse cardiovascular events relative to the general population that was unaccounted for by conventional cardiovascular risk factors. These findings highlight the need for closer surveillance of patients with mild to moderate ACHD and further investigation into management and mechanisms of cardiovascular risk unique to this growing population of high-risk adults. Abstract : Supplemental Digital Content is available in the text.